SISTEM KESENIAN MASYARAKAT BADUY - Putri Fajriani; Sapriya; Encep Supriatna; Resti Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to understand the art system of the Baduy community through a qualitative approach with ethnographic methods. The researcher explores the cultural values, artistic practices, and functions of art in the daily life of the Baduy people. Data were collected through participatory observation, in-depth interviews, and documentation. The results of the study show that the art system of the Baduy community is closely related to customs, spirituality, and environmental sustainability. Art in the Baduy community not only functions as a cultural expression but also as a medium for teaching life values.